2019
DOI: 10.2169/internalmedicine.1401-18
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Cryopyrin-associated Periodic Syndrome in an Elderly Woman with <i>NLRP3</i> and <i>MEFV</i> Mutations

Abstract: We herein report a case of a 75-year-old woman who presented with a low-grade fever, repeated cold-induced urticaria, and painful leg edemas with neutrocytosis. Because her mother also had cold-induced urticaria and her skin lesions histologically showed neutrophilic dermatitis, we suspected that she had familial cold autoinflammatory syndrome, a subtype of cryopyrin-associated periodic syndromes. Sequencing of the NLRP3 and MEFV genes revealed that she carried bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Remarkably, additional variants in the Mediterranean fever ( MEFV ) gene, encoding the pyrin protein, were detected in three patients (P24, P27, and P28) with p.E250K mutation (Table 2). 13 P27 and P28 had p.E148Q mutation in MEFV , which is commonly detected in familial Mediterranean fever (FMF) patients 13,15 . A recent article reported that two siblings suffering from FMF were detected with mutation p.M680I in the MEFV gene and rare missense mutation p.Val408Ile in the PSTPIP1 gene 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, additional variants in the Mediterranean fever ( MEFV ) gene, encoding the pyrin protein, were detected in three patients (P24, P27, and P28) with p.E250K mutation (Table 2). 13 P27 and P28 had p.E148Q mutation in MEFV , which is commonly detected in familial Mediterranean fever (FMF) patients 13,15 . A recent article reported that two siblings suffering from FMF were detected with mutation p.M680I in the MEFV gene and rare missense mutation p.Val408Ile in the PSTPIP1 gene 16 .…”
Section: Discussionmentioning
confidence: 99%
“…13 P27 and P28 had p.E148Q mutation in MEFV, which is commonly detected in familial Mediterranean fever (FMF) patients. 13,15 A recent article reported that two siblings suffering from FMF were detected with mutation p.M680I in the MEFV gene and rare missense mutation p.Val408Ile in the PSTPIP1 gene. 16 The association between MEFV and PSTPIP1 variants remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To date, colchicine therapy has not been systematically studied for CAPS and low-penetrance variants. A recent case report documented colchicine effectiveness in an elderly women with cold-induced urticarial-like rush and a pathogenic NLRP3 variant (A439V) and an additional MEFV variant (E148Q) [ 27 ]. Among 94 CAPS patients analysed in the Eurofever Registry none was treated with colchicine [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…All three forms are caused by the same gene, NLRP3 [ 4 , 5 ]. The prevalence of CINCA/NOMID syndrome is estimated to be 1 in 1,000,000, and approximately 40 people were diagnosed with CINCA/NOMID syndrome in Japan [ 6 ]. Although the first symptoms of CINCA/NOMID syndrome may be present at birth, there are few reports on the involvement of the placenta and umbilical cord in the disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%